Transcriptional termination signals for RNA polymerase II in fission yeast. - Birse, C; Lee, B; Hansen, K; Proudfoot, N (1997)
Transcription 'run-on' (TRO) analysis using permeabilized yeast cells indicates that transcription terminates between 180 and 380 bp downstream of the poly(A) site of the Schizosaccharomyces pombe ura4 gene. Two signals direct RNA polymerase II (pol II) to stop transcription: the previously identified 3' end formation signals located close to the poly(A) site and an additional downstream element (DSE) located at the region of termination. The downstream signal (135 bp) appears to act by pausing the elongating polymerase. TRO analysis indicates that elevated levels of transcribing polymerases accumulate over the DSE and that removal of this signal leads to transcription proceeding beyond the normal termination region. Furthermore, when inserted between two competing polyadenylation signals, this DSE increases the utilization of upstream poly(A) sites in vivo. We show that polymerase pausing over an extended region of template ensures termination of pol II transcription close to the poly(A) site.